ANTAGONISITAS DAN EFEKTIVITAS Trichoderma sp DALAM MENEKAN PERKEMBANGAN Phytophthora palmivora PADA BUAH KAKAO - Umrah Umrah; Tjandra Anggraini; Rizkita Rachmi Esyanti; I Nyoman P. Aryantha (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The purpose of the study was to select several Trichoderma sp based on its sporalation capabilities, and antagonistic character, and effectiveness to control P. palmivora on cocoa pod.  The study consisted of two stages. In the first stage, a Completely Randomised design was used which consisted of seven treatments with three replicates: T. viridae, collection of  Laboratory of Plant Pest and Diseases of Bogor Institute of Agriculture (T-A), T harzianum, collection of Laboratory of Plant Pest and Diseases of Bogor Institute of Agriculture (T-B), T harzianum,  collection of  Coffee and Cacao Research centre of Jember (T-C), T koningii, collection of  Coffee and Cacao Research Centre of Jember (T-D), T. Trichoderma sp 1, collection of Laboratory of Microbiology  Life Sciences Centre of Bandung Institute of Technology    (T-E), Trichoderma sp 2, collection of Laboratory of Microbiology  Life Sciences Centre of Bandung Institute of Technology (T-F) and Trichoderma sp, collection of Laboratory of Plant Pest and Diseases University of Tadulako (T-G). Parameters measured were sporulation capability of Trichoderma sp, percentage of antagonisticity of Trichoderma sp towards in vitro P. palmivora . The second stage of the study was to determine the effectiveness of Trichoderma antagonisticity, either individual or mixed cultures in controlling the development of  P. palmivora on cocoa pod. The study was designed with seven treatments with three replicates:  T-D, T-E, T-G, T-DE  (mixed culture of T-D and T-E),  T-DG  (mixed culture of T-D and T-G), T-EG ( mixed culture of T-E and T-G), T-DEG (mixed culture of  T-D, T-E, and T-G). The results of the study showed that at in vitro condition the kinds of Trichoderma sp which had the highest antagonisticity on P. palmivora were  Trichoderma sp (T-G, T-E and T-D). They were effective to control P. palmivora on cocoo pod either in individual or mixed cultures.  However, T-G will be further developed due to its highest effectiveness as a biological control compared to the others.